A8.09 Trained immunity in monocytes from rheumatoid arthritis patients and healthy individuals. (24th February 2016) - Messemaker, TC; Mikkers, HMM; Huizinga, TW; Toes, REM; van der Helm- van Mil, AHM; Kurreeman, F
Abstract : Background and objective: Rheumatoid Arthritis (RA) is a heterogeneous disease affecting approximately 1–2% of the European population. Development of RA is affected by both genetic and environmental triggers. In the present study we hypothesised that these environmental triggers might induce changes in the epigenome of immune cells. A concept that describes such a mechanism is known as 'trained immunity', which shows that isolated monocytes previously exposed to micro-organisms display elevated H3K4me3 on the promotor regions of immune genes resulting in enhanced RNA- and protein levels of TNFa and IL6 upon re-stimulation with inflammatory triggers. The phenomenon that innate cells triggered by past insults more readily react to new non-specific stimuli could contribute to the onset of auto-immunity. We wished to test whether the innate immune system of RA patients displays signs of "trained immunity" by analysing immune responsiveness and epigenetic changes of CD14 + monocytes isolated from both untreated RA patients and age-matched healthy controls. Methods: CD14 + monocytes were isolated from both untreated RA patients and age-matched healthy controls. Secreted TNFa and IL6 levels were measured using ELISA in the supernatant of naïve and LPS-stimulated monocytes from both RA patients and non-RA controls. RNA levels of TNFa and IL6 in naïve and LPS-stimulated monocytes from both groups were examined using RT-qPCR. Results: Both RNA and protein levels of TNFa and IL6 were low in unstimulated monocytes isolated from RA patients and healthy controls but no large differences were observed. After LPS-stimulation, the relative RNA levels (expressed in fold change relative to household gene) increased but were similar between patients and controls for TNFa (RA: 1.7 ± 0, 4, non-RA: 1.8 ± 0.9) and IL6 (RA: 2.9 ± 1, 3, non-RA: 3.3 ± 2.6). Concordantly, no large differences were detected for secreted cytokine levels, although secreted TNFa (RA: 4.3ng/ml ± 2.9, non-RA: 2.8ng/ml ± 2.6) and IL6 (RA: 67.2mg/ml ± 14.6, non-RA: 50.8mg/ml ± 17.3) levels seem slightly elevated in RA monocytes. Conclusions: In general, we could not detect large differences on RNA level or protein level of TNFa and IL6 between RA and non-RA patients. Therefore, we did not find evidence that the concept of trained immunity may contribute to the development of RA.